ANALISIS KESESUAIAN GERAK TENDANGAN SABIT PADA ATLIT PENCAK SILAT PERGURUAN PERISAI DIRI KECAMATAN WEDUNG - Bakhtiar, Ananda; Irawan, Fajar Awang (Universitas Negeri Surabaya, 2023)
This study aims to determine the development of the athlete's sickle kick in accordance with the mechanical studies needed so that improvements can be made and competitors can perform the sickle kick more realistically and limit injuries. The reason for this research is to examine the biomechanics, and the suitability of the sickle kick movement in martial arts athletes at the Perisai Diri College, Wedung District. The total population in this study were 10 participants in a fighting technique competition from Perisai Diri, Wedung District. This study uses a purposive sample method. The development of the martial arts sickle kick from the tide position stage, take-off stage to the effect stage is the focal point of the article in this review. The retrieval technique used in this research is quantitative explanation. The procedure for collecting information uses documentation techniques. The results of this study indicate that based on a biomechanical analysis of the suitability of the motion of the sickle kick, it is included in the